Role of MXenes/Polyaniline Nanocomposites in Fabricating Innovative Supercapacitor Technology - Majumdar, Dipanwita (Advanced Energy Conversion Materials, 2021)
Versatile and exclusive electronic, optical, physicochemical, electrochemical and mechanical features of both conducting polymers and MXenes have stimulated global scientists to take serious impetuses in designing innovative high-performance energy storage systems with these materials, for resolving the growing needs for auto-powering mechanically flexible and wearable electronics for all essential technological fields. However, both the materials have experienced some serious practical limitations, which have driven the scientific community to look for necessary modifications in the form of MXenes/PANI nanocomposites with suitable compositions that would essentially restore their representative characteristics but successfully suppress their functional drawbacks concurrently and considerably. Accordingly, in the present overview, the different strategies of fabrication of MXenes/PANI nanocomposites for advanced supercapacitors with special reference to the necessary morphological modifications brought about by synthetic improvisations that resulted in superior capacitive, electronic charge transport as well as structural properties have also been recognized and compared. Such analysis would purposefully assist in adjusting the integral mechanical and electrochemical responses for scheming smarter and highly flexible microelectronics soon.